IMPROVING STUDENTS’ VOCABULARY ACHIEVEMENT THROUGH JIGSAW MODEL OF TEACHING AT FOURTH SEMESTER OF NURSING ACADEMY OF HELVETIA MEDAN - Zuindra Zuindra (BAHAS, 2018)
This paper is the result of a study related to Class Action Research (CAR) conducted by using qualitative descriptive approach which focused on the analysis of collected data.  This paper concerns with the improvement of vocabulary achievement used Jigsaw model of teaching formulated by Aronson in 1978. This model of teaching uses several cycles in conducting the treatments. If the first cycle cannot achieve the targeted score, the next cycles can be conducted again. This Class Action Research was conducted at Nursing Academy of Helvetia Medan for Fourth Semester Students. This paper aims at establishing the teaching and learning process which make students more active and creative in applying English skills especially vocabulary skill. The result shows that the implementation of Jigsaw model of teaching is very effective to achieve more than the minimum standard of the score (passing grade) in the learning process. This study finds that cooperative learning by using Jigsaw model of teaching can increase motivation of the students to study English especially English vocabularies.